Analysis of anatomical landmarks of the mandibular interforaminal region using CBCT in a Brazilian population - Paloma Rodrigues Genú; Ricardo José de Holanda Vasconcellos; Bruna Paloma de Oliveira; Bruna Caroline Gonçalves de Vasconcelos; Nádia Cristina da Cruz Delgado (Universidade Estadual de Campinas, 2010)
Aim: To evaluate the position, presence, appearance and extent of various anatomical landmarks in the mandibular interforaminal region of Brazilian patients using cone-beam computed tomography (CBCT). Methods: A total of 142 CBCT examinations were analyzed to determine the most common location of the mental foramen (MF), the presence and extent of the anterior loop (AL) of the inferior alveolar nerve, and the appearance and length of the incisive canal (IC). The presence of sexual dimorphism and differences with relation to the left and right sides were also evaluated. Results: Most of the MF (45.5%) was located below the second premolar. The AL and the IC were observed in 18.9 and 96.5% of the images respectively. The average length of AL and IC was 3.14±1.25 mm and 13.68±5.94 mm respectively. No significant differences (p>0.05) between genders or left and right sides were observed for all evaluated parameters. Conclusions: The most common location of the MF, the high rate of visualization of the IC and the occasional presence of AL in the studied Brazilian population demonstrate the importance of using threedimensional images of the mandibular anterior region, allowing proper surgical planning and preventing injury to the neurovascular bundle.